Holocene Ostracods from the Hang Hau Formation in Lei Yue Mun, Hong Kong, and their palaeoenvironmental implications. Issue 2 (3rd April 2019) - Wang, He; Zhang, Haichun; Cao, Meizhen; Horne, David J.
Abstract : Wang . H., Zhang, H., Cao, M. & Horne, D.J., October 2018. Holocene Ostracods from the Hang Hau Formation in Lei Yue Mun, Hong Kong, and their palaeoenvironmental implications. Alcheringa 43, 320–333. ISSN 0311-5518. The Holocene Hang Hau Formation is the youngest part of the Quaternary succession in Hong Kong and yields abundant and diverse ostracods. This study of ostracod assemblages from two cores in Lei Yue Mun identifies eight genera and nine species of marine Ostracoda that were previously unreported from the Hang Hau Formation, increasing the known diversity from 67 to 76 species. Among these species, Neocyprideis timorensis (Fyan 1916) is reported for the first time in China. The recovery of abundant juvenile and adult specimens has facilitated illustration and discussion of an ontogenetic series for Neomonoceratina delicata Ishizaki & Kato, 1976, extending from the A-5 instar (fourth moult after hatching) to the sexually dimorphic A (adult) instar. Palaeoenvironmental analysis of the ostracod assemblages supports and strengthens previous interpretations indicative of a warm, shallow, nearshore-marine environment. He Wang[wang0701@163.com] State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology and Center for Excellence in Life and Paleoenvironment, Chinese Academy of Sciences, 39 East Beijing Road, Nanjing 210008, PR China; Haichun Zhang[hczhang@nigpas.ac.cn] State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology and Center for Excellence in Life and Paleoenvironment, Chinese Academy of Sciences, 39 East Beijing Road, Nanjing 210008, PR China; Meizhen Cao[mzcao@nigpas.ac.cn] Nanjing Institute of Geology and Palaeontology and Center for Excellence in Life and Paleoenvironment, Chinese Academy of Sciences, 39 East Beijing Road, Nanjing 210008, PR China; David J. Horne[d.j.horne@qmul.ac.uk] School of Geography, Queen Mary University of London, Mile End Road, London E1 4NS, UK. *Also affiliated with: University of Science and Technology of China, No. 96, JinZhai Road Baohe District, Hefei, Anhui 230026, PR China.